2022
DOI: 10.1002/ajoc.202200315
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Glycouronamides by Transamidation Approach at Room Temperature

Abstract: Synthesis of various glycouronamides via transamidation reaction is reported under mild reaction conditions. Transamidation of N-nitroso uronamides with primary and secondary amines was successfully achieved in the presence of triethyl amine. On the other hand, N-Boc uronamides underwent transamidation smoothly with various primary amines in the presence of DBU. These reactions provided the desired glycouroamides in good to excellent yields at room temperature.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 81 publications
0
3
0
Order By: Relevance
“…3 In the endeavour to achieve transamidation with a broad substrate scope, activation of amides prior to transamidation has been recognized as the most effective and successful method, 1,[3][4][5] in which the amides are activated by coupling an electron-withdrawing group to the amide nitrogen. [6][7][8][9][10][11][12][13][14][15][16][17][18][19] In recent years, transamidation of N-activated acyclic twisted amides has gained wide attention. Among them, the most notable ones are the transition-metal-free transamidations using LiHMDS, 1 Et 3 N, 9,19 DBU, 9,17 TBHP, 20 CsF, 21,22 and CsCO 3 23 and under catalyst-free conditions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…3 In the endeavour to achieve transamidation with a broad substrate scope, activation of amides prior to transamidation has been recognized as the most effective and successful method, 1,[3][4][5] in which the amides are activated by coupling an electron-withdrawing group to the amide nitrogen. [6][7][8][9][10][11][12][13][14][15][16][17][18][19] In recent years, transamidation of N-activated acyclic twisted amides has gained wide attention. Among them, the most notable ones are the transition-metal-free transamidations using LiHMDS, 1 Et 3 N, 9,19 DBU, 9,17 TBHP, 20 CsF, 21,22 and CsCO 3 23 and under catalyst-free conditions.…”
Section: Introductionmentioning
confidence: 99%
“…[6][7][8][9][10][11][12][13][14][15][16][17][18][19] In recent years, transamidation of N-activated acyclic twisted amides has gained wide attention. Among them, the most notable ones are the transition-metal-free transamidations using LiHMDS, 1 Et 3 N, 9,19 DBU, 9,17 TBHP, 20 CsF, 21,22 and CsCO 3 23 and under catalyst-free conditions. 5,10,14,[23][24][25][26][27] To date, transamidation has been primarily achieved with N-activated amides endowed with significant amide bond twists.…”
Section: Introductionmentioning
confidence: 99%
“…[12][13][14] On the other hand, Szostak and co-workers have demonstrated the transamidation of N-tert-butoxycarbonyl (N-Boc), 15,16 N-toluenesulphonate (N-Ts) activated secondary amides with palladium, [17][18][19][20] base catalysts, 21 and recently in the absence of any additives under mild conditions. 22 Recently the transamidation of N-Boc, N-nitroso, N-tosyl, and N-pivaloyl activated primary and secondary amides have been reported without any catalyst under mild conditions [23][24][25][26][27][28] and Xile Hu et al reported the nickel-catalyzed reductive transamidation of secondary amides with nitroarenes as the nitrogen source. 29 Microwave irradiation (MWI) is a non-conventional and environmentally friendly energy source and have been successfully employed recently to promote organic transformations.…”
mentioning
confidence: 99%